Agricultural Bio-Inputs as an Innovative Area of Opportunity for Agro-Industrial Growth in Developing Countries: Lessons from Argentina - da Silva Medina, Gabriel (2023)
Technology-based innovations in the bio-economy are expected to provide new market opportunities for agro-industrial growth in developing countries. This study explores how domestic entrepreneurs have been benefiting from the growing global demand for sustainable agribusiness by establishing themselves in the agricultural bio-inputs sector. Aiming to explore how developing countries can build agro-industrial capabilities that go beyond farming, a case study was conducted in Argentina giving the country’s large domestic market for agricultural inputs. The assessment was based on official data and a survey conducted with a sample of 14 Argentinean companies. Results revealed a growing number of domestic companies in the bio-inputs market, which accounted for 74% of the total number of companies by 2022. Contextual aspects that favored domestic players include private investments by local entrepreneurs, the use of locally available technologies, support from public innovation centers and assertive market strategies. Principal component analysis revealed different business models, which include companies focusing on the development of new products, companies with professional industrial plants for large-scale production and companies with a strong marketing component reaching out to farmers. The global growth of sustainable bio-based agricultural production offers areas of opportunities for domestic investments in cleaner agro-industrial sectors that go beyond the primary production of commodities and can build industrial capabilities in developing countries.